Oral Corticosteroid Therapy in Leprosy's new patients with Type 2 Reaction - Irma Tarida Listiyawati; Sawitri Sawitri; Indropo Agusni; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Leprosy type 2 reactions is an acute inflammatory episode in lepromatous leprosy patient that ascociated with deposition of immune complexes. Standard regiment for severe reaction is corticosteroid. Almost Leprosy type 2 reactions patients become chronic and recurrent so it implicates to more complications if it was not managed well. Purpose: To determine the distribution of type 2 reactions patients which treated with oral corticosteroid in leprosy division of dermatovenereology outpatient clinic of Dr. Soetomo General Hospital. Methods: Retrospective study using new patient's medical record during the period of January 1 2009 until December 31 2013 and the observation continued until December 31 2013. Results: The total type 2 reactions patients with oral corticosteroid was 112 patients, mostly were male aged between 25-64 years and has the Lepromatous Leprosy (LL) type (33%), the reactions happened after RFT (43.8%), 65.2% had metil prednisolon medication, the initial equivalent dose was 30 mg in 32.1% patient. 21.4% patient had more than one cycle of corticosteroid therapy and 8.9% patient had the steroid side effect. Conclusion: Leprosy's type 2 reactions tend to be chronic and recurrent and the impact were patients got longterm continuously corticosteroid medication, so the patients need to be monitored including side effects.Key words: leprosy's type 2 reaction, oral corticosteroid, side effects.